Carter W. R. Will I Be a Dead Person? / trans. from Engl. A. V. Nekhaev - A. V. Nekhaev (Омский научный вестник: Серия "Общество. История. Современность")
Eric Olsen argues from the fact that we once existed as fetal individuals to the conclusion that the Standard View of personal identity is mistaken. I shall establish that a similar argument focusing upon dead people opposes Olson’s favored Biological View of personal identity